DEPARTURE FROM THE TRADITIONAL LIVELIHOOD: A STUDY ON PUROIKS OF KURUNG KUMEY DISTRICT, ARUNACHAL PRADESH - Ramya, Tame (PEOPLE: International Journal of Social Sciences, 2017)
The Puroiks are traditional occupational group in Kurung Kumey district of Arunachal Pradesh inhabiting in about 20 villages. Hunting and gathering is their main livelihood. They use their indigenous knowledge and techniques to hunt animals and gather food stuffs from the dense forest. It is their popular livelihood and income. Presently lots of issue affects their traditional livelihood. They try to hold on to their profession but poor socio-economical condition compels them to change their traditional way of earning. Some external and internal social, economic, and environmental pressures are responsible for this change. At the same time, new generation does not give any positive response in favour of this profession. So, the tendency is very clear that it will change in near future. In this study, I try to find out the responsible socio-economic conditions of present scenario behind the changing patterns of traditional livelihood of Puroiks community.